2020
DOI: 10.3390/plants9121796
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellic Acid Modifies the Transcript Abundance of ABA Pathway Orthologs and Modulates Sweet Cherry (Prunus avium) Fruit Ripening in Early- and Mid-Season Varieties

Abstract: Several phytohormones modulate ripening in non-climacteric fruits, which is triggered by abscisic acid (ABA). Gibberellins (GAs) are present during the onset of ripening in sweet cherry fruits, and exogenous gibberellic acid (GA3) application delays ripening, though this effect is variety-dependent. Although an ABA accumulation delay has been reported following GA3 treatment, the mechanism by which GA modulates this process has not been investigated at the molecular level in sweet cherry. Therefore, the aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…Previously the role of ABA on sweet cherry fruit maturity has usually been studied in early-maturing cultivars (Satonishiki, Hongdeng, Prime Giant) 13,16,23 , with only a few experiments in other mid-maturing cultivars such as 'Bing' 19 and 'Lapins' 17 . Regardless of this, the exogenous application is not a common agronomic practice in sweet cherry in comparison to other growth regulators such as gibberellin (GA3) 18,[24][25][26][27][28][29][30] . Furthermore, the genotypic effect on the ABA response has not been fully addressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously the role of ABA on sweet cherry fruit maturity has usually been studied in early-maturing cultivars (Satonishiki, Hongdeng, Prime Giant) 13,16,23 , with only a few experiments in other mid-maturing cultivars such as 'Bing' 19 and 'Lapins' 17 . Regardless of this, the exogenous application is not a common agronomic practice in sweet cherry in comparison to other growth regulators such as gibberellin (GA3) 18,[24][25][26][27][28][29][30] . Furthermore, the genotypic effect on the ABA response has not been fully addressed.…”
Section: Discussionmentioning
confidence: 99%
“…others have reported that GA3 treatment 17,18,29 and fluridone treatment increase the size of sweet cherry fruits 29 . A summary of the effects of the different ABA treatments in cultivars per season is shown in Table 1.…”
Section: Statistical Variations In the Physiologicalmentioning
confidence: 95%
See 1 more Smart Citation
“…Previously the role of ABA on sweet cherry fruit maturity has usually been studied in early-maturing cultivars ('Satonishiki', 'Hongdeng', 'Prime Giant') [11,14,21], with only a few experiments in other mid-maturing cultivars such as 'Bing' [17] and 'Lapins' [15]. Regardless of this, the exogenous application is not a common agronomic practice in sweet cherry in comparison to other growth regulators such as gibberellin (GA 3 ) [16,[22][23][24][25][26][27][28]. Furthermore, the genotypic effect on the ABA response has not been fully addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the consistent decrease in fruit size (width and weight) in ABA canopy sprayed 'Lapins' sweet cherry fruits at harvest, versus the seasonal variations associated with the 'Glenred' cultivar, may be associated with the differential response that early-and mid-maturing cultivars have to additional phytohormones such as gibberellic acid. Recently we have reported the GA 3 modifies the transcript abundance of ABA pathway orthologs and modulates sweet cherry fruit ripening in early-and mid-maturing cultivars [16] and that there is a differential transcriptional response between these cultivars treated with GA 3 [28].…”
Section: Cultivar Dependent Effect Of Aba Canopy Spraying Of Sweet Cherry Trees On Fruit Quality Parametersmentioning
confidence: 99%